The impact of self-assessment-based learning modules on academic achievement of Hindu religious education students in Sangiang language courses - Dana, I Wayan; Nitiasih, Putu Kerti; Ariawan, Putu Wisna; Parmiti, Desak Putu (Edelweiss Applied Science and Technology, 2024)
Teaching materials play an important role in improving the quality of learning and student learning outcomes. Therefore, this study aims to evaluate a self-assessment-based learning module developed for the Sangiang language course for students majoring in Hindu religious education. Specifically, this study aims to identify the effect of the module on student learning achievement in the Sangiang language course. This study used an experimental approach with a post-test-only control group design. Two classes were used as samples in this study, and they were selected using statistical matching. One class became the experimental class, and the other became the control class. Data were collected using multiple-choice tests, which have proven valid and reliable. The test was distributed to the experimental and control classes after the module was implemented in 8 meetings in the experimental class and after the control class was taught using conventional materials. The collected data were analyzed quantitatively using descriptive and inferential statistics. From the results of descriptive statistics, it was found that there were differences in learning outcomes between the experimental and control groups, where the experimental class obtained higher learning outcomes. However, because the data were not normally distributed, inferential statistical analysis, which was used to identify that the differences in learning outcomes of the experimental class and the control class were significant, was carried out using Mann-Whitney. From the analysis carried out, it was found that the differences between the control class and the experimental class were proven to be significant. Thus, it can be concluded that the developed module has proven to significantly influence student learning achievement in the Sangiang Language course.